The Evolution of the Complex Anticlinal Belt With Crosscutting Strike‐Slip Faults in the Central Tarim Basin, NW China. Issue 6 (24th June 2019) - Qiu, Huabiao; Deng, Shang; Cao, Zicheng; Yin, Ting; Zhang, Zhongpei
Abstract: Integrated 2‐D and 3‐D seismic data sets reveal that a WNW trending complex anticlinal belt (the Tazhong Uplift) was cut roughly perpendicularly by a series of NNE oriented strike‐slip faults in the central Tarim Basin, NW China. Through detailed interpretation of the internal architecture of the Tazhong Uplift and the structural characteristics of the strike‐slip faults, the timing of their movements was determined. Based upon their geometric relationship and coeval movement, we propose an integrated model for the evolution of both the Tazhong Uplift and the strike‐slip fault system. Initially, the Tazhong Uplift formed perpendicular to the NNE oriented compression that responded to the collision between the Tarim block and the western Kunlun terrane in the latest Middle Ordovician. Meanwhile, regional joints formed parallel to the maximum compression, that is, perpendicular to the Tazhong Uplift. In the latest Ordovician, northward compression caused the uplifting climax of the Tazhong Uplift in response to the collision between the Tarim block and the coherent eastern Kunlun‐Altyn Tagh‐Qaidam‐Qilian terrane. Under such a northward compression, the resolved shear stress on the NNE trending joints formed the transpressional strike‐slip faults. Afterward, the Tazhong Uplift tilted northward during the ongoing subduction from the Kunlun Ocean, which lasted until the latest Middle Devonian. The negative flower structures formed along the preexisting transpressional strike‐slip faults due to the dragging of the overlying covers in the latest Middle Devonian. The data and evolution model not only unveil the formation mechanism of the Tazhong Uplift and the associated strike‐slip faults but also provide further constraints on the evolutionary age of the Proto‐Tethys Ocean. Key Points: Seismic reflection data reveal that a complex anticlinal belt was cut roughly perpendicularly by a series of left‐lateral strike‐slip faults The evolution of the strike‐slip fault system is coeval with that of the complex anticlinal belt The Tazhong Uplift with crosscutting strike‐slip faults evolved in response to the Proto‐Tethys tectonic evolution